Optmization of exposure parameters in digital mammography (CR) using figure of merit - Isabela Soares de Morais; Peterson Lima Squair; Maria do Socorro Nogueira Tavares (Brazilian Journal of Radiation Sciences, 2021)
A high diagnostic standard associated with the lowest radiation dose possible for the patient is the aim for a quality examination in mammography, this can be achieved through the Figure of Merit which is a parameter used for optimization in digital mammography. The objective of this work is to determine the optimized radiographic technique (kV and anode / filter combination) for the CR detection system (Computerized Radiography),  using the parameter of the figure of merit (FOM), from the contrast noise Ratio (CNR)  and the average glandular dose (AGD), with two breast simulators (PMMA and CIRS) and perform a comparison between them. The optimization process was performed on the Siemens Mammomat 3000 Nova Mammograph and the Kodak Direct View CR 850 System CR scanning system using two breast, PMMA and CIRS simulators in the following thicknesses: 2, 4.5 and 7 cm. In order to calculate the AGD, the incident air kerma (Ka,i) was measured and the X-ray beam characteristic factors were applied, according to the technical parameters used for each exposure performed in the simulators. With the values of AGD and CNR associated with each image, the technique optimized for the mammograph-CR set was calculated using the figure of merit. Both simulators presented similar FOM for the conditions tested, but should not be considered equivalent. The following X-ray spectra were selected (anode / filter combination): 2 cm thick (Mo / Mo), 4.5 cm thick (W / Rh) and 7 cm (W / Rh). The estimated doses referring to the optimized techniques found in this work respected the acceptable reference levels in international protocols for quality control in mammography.